REPRESENTASI NILAI-NILAI PENDIDIKAN KARAKTER PADA FILM RIKO THE SERIES “MABAR BOLEH, ASAL…” - Cahyami, Hartika; Mulyadiprana, Ahmad; Merliana, Anggit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the representation of character education values that appear in the animated film Riko The Series in the episode “Mabar Boleh, Asal...” (Playing Together is Okay, As Long As...). This study employs a qualitative approach using content analysis. It is a non-subjective study. The focus of observation is how the educational values depicted in the program align with the 18 character education values outlined by the Ministry of Education and Culture. The results indicate that the animated film Riko The Series effectively represents character education values, making it a valuable tool to support the learning process, particularly in character education.